HUBUNGAN ANEMIA PADA IBU HAMIL ATERM DENGAN BERAT LAHIR PLASENTA DAN BERAT LAHIR BAYI DI RSU KOTA KUPANG TAHUN 2014 - IGNASENSIA DUA MIRONG; NI LUH MADE DIAH PUTRI ANGGARAENINGSIH (Jurnal Kebidanan: MIDWIFERY MEDICAL JOURNAL, 2014)
Anemia of pregnancy women is a problem health related on the high incidence and complication can occure mather and fetus. In the world 34 % pregnant women with anemia, whereas 75 % in developed country (WHO, 2005 in Syafa 2010). In Indonesia, 63,5% pregnant women have anemia (Saifuddin, 2006), in NTT 46,2% preganan women have anemia (health agency of NTT Province,2013) and in RSUD Kota Kupang 25,6 % preganant women have anemia (MR RSUD Kota Kupang, 2014). From the pregnant women who have anemia 62,3% of them have iron deficiency anemia (IDA) (Wiknjosastro,2005). Aterm pregnant women inclined have IDA because in that term fetus heap iron reserve for himself. (sin sin 2008) Pregnant women with anemia had oksigenasi disorder and food from mother to fetus through placenta. And can influence the placenta function. The deacrease of placenta function can make fetal growing disruption, abortus, prolonged delivery, sepsis puerperalis, maternal death and fetal death. Objective : to knowing correlation anemia from aterm preganant women with the placenta weight and baby weight in RSUD Kota Kupang 2014.Method, This research using cross sectional design with 30 sampel, and accidental technik.Conclution : There is no correlation between anemia with the palcenta weight. This is because the preganant women are in light anemia katagory. And no significant correlation between anemia with the baby weight.